Complexing Ability of N-[2-(2-Morpholinoacetyl)hydrazinocarbothioyl]benzamide Toward Iron(II) Ions - Amerkhanova, Sh.K.; Nurkenov, O.A.; Fazylov, S.D.; Shlyapov, R.M.; Gavrilenko, M.A.; Bekkulina, F.Zh. (Springer, 2013)
Qualitative and quantitative assessment of the complexing ability of N-[2-(2-morpholinoacetyl)hydrazinocarbothioyl]benzamide toward iron(II) ions is given. Stability constants of iron(II) complexes are determined. Thermodynamics of the complex-formation processes is considered.